2016
DOI: 10.1002/hed.24441
|View full text |Cite
|
Sign up to set email alerts
|

Impact of p16 expression, nodal status, and smoking on oncologic outcomes of patients with head and neck unknown primary squamous cell carcinoma

Abstract: Among patients with CUP, p16-positive status is an independent predictor of DFS but not overall survival (OS). © 2016 Wiley Periodicals, Inc. Head Neck, 2016 © 2016 Wiley Periodicals, Inc. Head Neck 38: 1347-1353, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 33 publications
3
52
1
2
Order By: Relevance
“…Keller et al [58] reported on even more pronounced survival differences in p16 positive compared to p16 negative patients (5y OS 92% vs 30% and 5y DSS 92% vs 60%) [58]. Similar results were demonstrated by Jensen et al [57], Schroeder et al [27] and Axelsson et al [64], whereas Tribius et al [55] and Dixon et al [65] did not find any survival difference. In contrast to some [1,2,27,[66][67][68] but in line with other reports [54,56] nodal stage did not have an impact on survival in our cohort.…”
Section: Discussionsupporting
confidence: 69%
“…Keller et al [58] reported on even more pronounced survival differences in p16 positive compared to p16 negative patients (5y OS 92% vs 30% and 5y DSS 92% vs 60%) [58]. Similar results were demonstrated by Jensen et al [57], Schroeder et al [27] and Axelsson et al [64], whereas Tribius et al [55] and Dixon et al [65] did not find any survival difference. In contrast to some [1,2,27,[66][67][68] but in line with other reports [54,56] nodal stage did not have an impact on survival in our cohort.…”
Section: Discussionsupporting
confidence: 69%
“…6,16,17,20 The male predominance correlates with the ease of female-to-male HPV transmission which is precipitated by the high number of sexual partners and oral sex encounters. 16,17,19,20,[22][23][24] However, one retrospective analysis of a small series of patients showed that the HPV status does not correlate with neck stage at presentation. The clinical N classification at diagnosis is usually N2/N3 (11%-95%).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…16,19,24,51,57,68 In these studies, HPV-related SCCUP has a good prognosis which constitutes the backdrop for separating this entity from non-HPV-related SCCUP. 16,19,24,51,57,68 In these studies, HPV-related SCCUP has a good prognosis which constitutes the backdrop for separating this entity from non-HPV-related SCCUP.…”
Section: Treatment Of Hpv-related Sccupmentioning
confidence: 99%
“…As a HPV surrogate marker, immunohistochemical staining of p16, a human tumor-suppressor protein [5965], is also widely used. Despite showing a significantly improved disease-free survival, some authors like Dixon et al could not find an improved overall survival for p16-positive HNCUP patients in their studies [66]. Other reports showed a significant positive impact of HPV/p16 only when combined with other factors like (non-)smoking [67].…”
Section: Introductionmentioning
confidence: 99%